Improving the use of research evidence in guideline development: introduction - Schünemann Holger J; Fretheim Atle; Oxman Andrew D (BMC, 2006)
Abstract In 2005 the World Health Organisation (WHO) asked its Advisory Committee on Health Research (ACHR) for advice on ways in which WHO can improve the use of research evidence in the development of recommendations, including guidelines and policies. The ACHR established the Subcommittee on the Use of Research Evidence (SURE) to collect background documentation and consult widely among WHO staff, international experts and end users of WHO recommendations to inform its advice to WHO. We have prepared a series of reviews of methods that are used in the development of guidelines as part of this background documentation. We describe here the background and methods of these reviews, which are being published in Health Research Policy and Systems together with this introduction.